Discovery, Total Synthesis and Key Structural Elements for the Immunosuppressive Activity of Cocosolide, a Symmetrical Glycosylated Macrolide Dimer from Marine Cyanobacteria. Issue 24 (3rd May 2016) - Gunasekera, Sarath P.; Li, Yang; Ratnayake, Ranjala; Luo, Danmeng; Lo, Jeannette; Reibenspies, Joseph H.; Xu, Zhengshuang; Clare‐Salzler, Michael J.; Ye, Tao; Paul, Valerie J.; Luesch, Hendrik
Abstract: A new dimeric macrolide xylopyranoside, cocosolide (1 ), was isolated from the marine cyanobacterium preliminarily identified as Symploca sp. from Guam. The structure was determined by a combination of NMR spectroscopy, HRMS, X‐ray diffraction studies and Mosher's analysis of the base hydrolysis product. Its carbon skeleton closely resembles that of clavosolides A–D isolated from the sponge Myriastra clavosa, for which no bioactivity is known. We performed the first total synthesis of cocosolide (1 ) along with its [ α, α ]‐anomer (26 ) and macrocyclic core (28 ), thus leading to the confirmation of the structure of natural1 . The convergent synthesis featured Wadsworth–Emmons cyclopropanation, Sakurai annulation, Yamaguchi macrocyclization/dimerization reaction, α‐selective glycosidation and β‐selective glycosidation. Compounds1 and26 potently inhibited IL‐2 production in both T‐cell receptor dependent and independent manners. Full activity requires the presence of the sugar moiety as well as the intact dimeric structure. Cocosolide also suppressed the proliferation of anti‐CD3‐stimulated T‐cells in a dose‐dependent manner. Abstract : Diving into symmetry : A new dimeric macrolide xylopyranoside, cocosolide, was isolated from marine cyanobacteria. Its structure was elucidated by a combination of spectroscopic methods and further confirmed by total synthesis (see figure). Along with its [ α, α ]‐anomer and macrocyclic core, cocosolide was evaluated in various bioassays, which unveiled its role in immunosuppression. SAR studies indicated the presence of the sugar moiety and the intact dimeric structure was required to achieve full activity.